Perancangan Aplikasi Penjualan Berbasis Client Server Pada Kedai WKWK Kota Purwokerto Menggunakan Metode Prototype - M Yoka Fathoni; Raditya Faisal Waliulu; Ardi Susanto; M Nishom (Politeknik Harapan Bersama, 2022)
Sales processes such as ordering and paying at the WKWK Kedai Purwokerto are still very manual, as is still using written notes and payment transactions are still carried out by manual calculations, this can result in errors in making payment transactions, so a Client Server-based sales application is made. With the creation of this application, the needs of admins and cashiers can make the ordering and payment process easy and fast and efficient. Sales application at Kedai WKWK Purwokerto City that can provide convenience in placing orders, payment transactions and managing important data in order to convey data information quickly, accurately and integratedly. A food and beverage sales application that was built on a Client Server basis, using the MySQL Database, Apache Web Server and PHP programming language, which is designed to handle the processing and management of data so as to produce reports in the form of master data, normative (numbers) and the matrix at Kedai WKWK Purwokerto City.